Breaking into venture : an outsider turned venture capitalist shares how to take risks, create power, and build life-changing wealth - Gates, Allison Baum (McGraw-Hill, 2023)
"Long-held secrets of the world's most elite VC investors revealed! Whether you're an investor, entrepreneur, or career-focused business professional, developing a venture capitalist (VC) mindset will give you the edge on the competition every time but VCs traditionally operate in a corner of finance cloaked in obscurity and secrecy. Now, Breaking into Venture draws the curtain on this exclusive club, providing priceless insights into how its members think and invest"--